(untitled) (London Journal of Research In Management & Business, 2025)
Comparative intellectual property law distinguishes between two systems of protection. On the one hand, the Copyright system, and on the other, the Droit d’auteur system. Through a process of legal acculturation, the opposition between these two systems has been transposed to Africa, despite similar cultures and socio-economic conditions. This opposition is tending to become less pronounced, but closer resemblances are worth considering.